Determinants of hypertensive disorders during pregnancy among women admitted to Bule Hora University Teaching Hospital, West Guji Zone, Southern Ethiopia - Amana Jilo; Nurye Sirage; Dube Jara; Zewdu Dagnew (Elsevier, 2024)
Introduction: Hypertensive disorder of pregnancy is a sign of an underlying pathology which, may be presented before pregnancy or developed after the mid gestational age of the pregnancy. There is limited information about determinants of hypertensive disorder of pregnancy in Ethiopia. This study is conducted to provide baseline information about determinants of hypertensive disorders of pregnancy among women admitted to Bule Hora Teaching Hospital, southern Ethiopia. Objectives: The aim of this study was to identify determinants of hypertensive disorders of pregnancy among women admitted to Bule Hora Teaching Hospital, southern Ethiopia, 2021. Methods: A facility based unmatched case control study was conducted from March 20 to April 20, 2021. Data were collected from available record (chart) from October1, 2017 to 30 September 2020. 393 mothers (131 cases and 262 controls) were selected. The collected data were entered into Epi data 3.1 and analysis was conducted using Stata version 14. All independent variables in bivariate analysis with a p-value ≤ 0.20 was included in the initial of multivariable analysis. In multivariable analysis a p-value < 0.05 was used to declare statistical significance. The results were presented using tables and pie chart based on the types of data. Results: The study revealed that age of the mothers, in which who belongs to age group 20-24 [AOR = 0.39,(95 % CI:0.17-0.88)], mothers ANC follow up greater than three [AOR = 0.51(95 %CI:0.28-0.90)], those mothers didn't have history of abortion [AOR = 0.32 (95 % CI:0.12-0.90] were less likely to develop hypertensive disorders during pregnancy and twin pregnancy [AOR = 7.9,(95 % CI:1.10-58.78)], mothers with blood group O [AOR = 4(95 % CI:1.76-9.22)] were more likely to develop hypertensive disorders during pregnancy. Conclusion: Age of the mother less than twenty years, having twin pregnancy, blood group O, having a history of abortion, and having less than three ANC follow up were significantly related with developing hypertensive disorders of pregnancy. During Antenatal diagnosis and management health professionals should conduct detail patient evaluation to identify the risk factors of HDP and to develop better treatment protocol. The governments and stakeholders should work to strengthen the ANC practice by including all possible contributing factors of HDP in the ANC follow up guidelines.